Evaluation of Biological Degraded Keratin for Biogas Production Using Dry Anaerobic Digestion System - Sinta Setyaningrum; Regina J Patinvoh; Ronny Purwadi; Mohammad Taherzadeh (Bandung State Polytechnic (Politeknik Negeri Bandung), 2021)
Anaerobic digestion is a methane gas production process that can be used as sustainable alternative energy. Anaerobic digestion utilized various types of organic waste as substrate for the reaction process. Keratin waste is an organic waste mainly produced from the poultry and farming industry. Pretreatment is usually required to hydrolyzed keratin protein complex as the amino acid is easily used as the substrate in anaerobic digestion reaction. Biological pretreatment was selected because it more energy saver and generating diverse types of amino acid monomers. Three types of keratins used in this research were feathers, wool, and hair. Culture of Bacillus sp. C4 were inoculated into keratins and incubated for 24 hours, 48 hours, and 72 hours. The chicken feathers produce the soluble protein as much as 7.23 mg/ml, 32.59 mg/ml and 45.99 mg/ml respectively, while the sheep wool produce 24.08 mg/ml, 36.73 mg/ml and 38.75 mg/ml respectively according to incubation time. Meanwhile, keratin hair cannot be degraded by Bacillus sp. C4 at all. Free ammonia formed by hydrolysis of proteins is suspected to be an inhibitor in the methanogenesis process, as total methane produced from degraded keratin only 256,6 ml C4/gr VS in 36 days retention time.